bellwetherreport.com: Trade Alert for Red Hat Inc (M2 Presswire, 2007)
All material herein was prepared by the Bellwetherreport.com, (Bellwether) based upon information believed to be reliable. The information contained herein is not guaranteed by Bellwether to be accurate, and should not be considered to be all-inclusive. The companies that are discussed in this opinion have not approved the statements made in this opinion. This opinion contains forward- looking statements that involve risks and uncertainties. This material is for informational purposes only and should not be construed as an offer or solicitation of an offer to buy or sell securities. Bellwether is not a licensed broker, broker dealer, market maker, investment banker, investment advisor, analyst or underwriter. Please consult a broker before purchasing or selling any securities viewed on or mentioned herein. Bellwether may receive compensation in cash or shares from independent third parties or from the companies mentioned. Red Hat's membership in the alliance builds on the interoperability work started by the JBoss Division 18 months ago to optimize JBoss Enterprise Middleware on the Windows platform. To date, those efforts have been primarily in the Web Services arena, including the critically important World Wide Web Consortium (W3C) WS-Addressing specification and several plugfests around WS- Security, WS-Transactions, and WS-Addressing. In addition, Microsoft completed Hibernate certification for Microsoft SQL Server 2005 Java Database Connectivity (JDBC) driver. Now, Red Hat can extend and deepen interoperability beyond standards to the native level on Windows for its JBoss Enterprise Middleware.